Essays in honor of Jerry Hausman - Hausman, Jerry A.; Baltagi, Badi H.; Newey, Whitney K.; White, Hal (Advances in econometrics ;, 2012)
A title that aims to annually publish original scholarly econometrics papers on designated topics with the intention of expanding the use of developed and emerging econometric techniques by disseminating ideas on the theory and practice of econometrics throughout the empirical economic, business and social science literature.